Differential targeting of GSH1 and GSH2 is achieved by multiple transcription initiation: implications for the compartmentation of glutathione biosynthesis in the Brassicaceae - Wachter, Andreas; Wolf, Sebastian; Steininger, Heike; Bogs, Jochen; Rausch, Thomas (The plant journal, 2004)
The genome of Arabidopsis thaliana reveals that in this species the enzymes of glutathione biosynthesis, GSH1 and GSH2, are encoded by single genes. In silico analysis predicts proteins with putative plastidic transit peptides (TP) for both genes, but this has not been experimentally verified. Here we report a detailed analysis of the 5′ends of GSH1 and GSH2 mRNAs and demonstrate the subcellular targeting of the proteins encoded by different transcript types. GSH1 transcript analysis revealed two mRNA populations with short and long 5′-UTRs, respectively, both including the entire TP sequence. The ratio of long/total GSH1 transcripts was subject to developmental regulation. Transient transformation experiments with reporter gene fusions, bearing long or short 5′-UTRs, indicated an exclusive targeting of GSH1 to the plastids. Corroborating these results, endogenous and ectopically expressed GSH1 proteins were always present as a single polypeptide species with the size expected for correctly processed GSH1. Finally, the plastidic GSH1 localization was confirmed by immunocytochemistry. Similar to GSH1, multiple transcript populations were found for GSH2. However, here the prevalent shorter transcripts lacked a complete TP sequence. As expected, the large (but less abundant) transcript encoded a plastidic GSH2 protein, whereas GSH2 synthesized from the shorter transcript was targeted to the cytosol. The implications of the results for the compartmentation and regulation of GSH synthesis are discussed.